Education on Utilizing Soy Milk Pulp into Healthy Snacks to Improve Family Economy in Mendalo Darat Village - Indah Mawarti; Kamariyah, Kamariyah (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Background: One of the types of legumes that has the highest protein content is soybeans, the nutritional content of whole soybeans is around 35-40% the highest protein, and has a complete content of essential Amino Acids compared to other types of beans. So many products from soybeans are used by the community and even companies process them into soy milk, in addition to tofu, tempeh and other products. The increase in demand and public interest in the need for soy milk as a source of vegetable protein, especially for people who are allergic to certain types of protein or do not like types of animal milk, makes soy milk dregs abundant. The waste that is abundant from the manufacture of soy milk in general is simply thrown away by the community. Although some are processed into animal feed, oncom tempeh and others. However, in general, people who process soy milk do not know about the processing of soy milk dregs. Even though the dregs still contain nutrients such as fiber, protein, minerals, monosaccharides & oligosaccharides, although each has a different content, because basically the quality of the protein from soy milk itself is not inferior to the protein content from cow's milk. This dregs if processed properly, can be sold and will add to the family's economic income besides selling soy milk, as well as selling food processed from soy milk dregs. Method: The method of implementing this activity is carried out in several stages, the first stage is a survey, making an approach on the willingness of residents to take part in the activity, then providing counseling education and technical guidance, manufacturing practices, counting and weighing and packaging, as well as marketing trials. Results: Involvement of residents to make processed soy milk dregs products into food until they are ready to be marketed. Processing of soy milk dregs is very easy to do, the additional ingredients are easy to get, and it has a delicious, savory, crunchy taste, and of course has a fairly good nutritional content, so this product needs to be developed both in terms of more attractive packaging and cheap packaging prices